Reducing Effects of Initial Imperfection by Investment in the Orthotropic Characteristics of Laminated Composite Plate - Wisam Hamzah Mohammed; Svetlana Shambina; Haider Kadhim Ammash (Salehan Institute of Higher Education, 2023)
The target of this study is to reduce the impact of initial imperfection on the nonlinear dynamical performance of laminated composite plates by taking advantage of the orthotropic characteristics of laminated composite plates by changing carbon fiber sawing in the mass matrix and fiber orientation with different patterns and studying the effect of this optimization without and with initial imperfection (Wo) and different aspect ratios (W/L) and various boundary conditions through analyzing the load-displacement responses for plates under axial in-plane compressive loads by using the FORTRAN 94 programming language. Von-Karman's assumptions are utilized to include geometric nonlinearity for nine node isoperimetric quadrilateral components with five degrees of freedom into the structural model, which is based on first-order shear deformation theory. The Newmarkâ€™s implicit time integration method and Newton-Raphson iteration concurrently are employed to solve the nonlinear governing equation in conjunction. The study proved the effectiveness of the carbon fiber's varying geometric distribution and the difference in its directions in reducing the negative effects of the initial imperfection on the large elastic-plastic displacement and critical buckling. To highlight the veracity of the results, some of them have been validated against those found in the literature review.Â Doi: 10.28991/CEJ-2023-09-07-03 Full Text: PDF